Brewed for Performance: Caffeine’s Impact on Nutrition, Endurance and Strength in Sports - Janiszewski, Michał; Komorowski, Marcin; Kaczorowski, Rafał; Hunia, Jaromir; Jurek, Jonasz; Kapciak, Alicja; Górny, Julia; Pelczarska, Aleksandra; Forenc, Tomasz (Journal of Education, Health and Sport, 2025)
Caffeine is one of the most widely consumed and studied stimulants worldwide with a long history in athletics as a performance enhancer. Although listed as a stimulant in the World Anti-Doping Agency’s (WADA’s) 2024 Monitoring Program, its use is not prohibited. Individual responses to caffeine vary widely due to factors like genetics, age, and lifestyle habits, such as smoking and diet. This paper examines caffeine’s multifaced role in human metabolism, with an emphasis on athletes’ training (endurance and strength) and post-exercise recovery. Our comprehensive review of literature indicates that caffeine typically ingested one hour before exercise in doses around 3-6 mg/kg raises metabolic rate, increases free fatty acids mobilization, extends time to exhaustion in running and cycling, improves maximal voluntary contraction and enhances high-speed muscular activity with low-load movements. It also blocks pain perception. These findings highlight caffeine’s role in endurance and strength sports. However, due to inconsistencies, further research is needed to develop exercise-specific protocols considering dose, timing, and training status. Caffeine aids recovery by reducing delayed - onset muscle soreness, improving glycogen resynthesis, and reducing fatigue. However, late consumption may affect sleep, requiring careful timing and dosage adjustments. Moreover, potential side and positive effects of caffeine ingestion need to be considered.